Evaluating the Effectiveness of the ABCDE Technique in Group Guidance to Reduce Hoax Behaviour Among Middle School Students - Rabiah Nasution; Ahmad Syarqawi (Journal of General Education and Humanities, 2025)
The proliferation of hoaxes among adolescents has emerged as a critical challenge in the digital era, driven by the high intensity of social media use and limited digital literacy skills. This study examines the effectiveness of group guidance using the ABCDE technique—derived from Rational Emotive Behaviour Therapy (REBT)—in reducing hoax-spreading behaviour among junior high school students. A pretest–posttest one-group design involved a purposive sample of eight eighth-grade students at SMP Negeri 2 Panyabungan. Data were collected using a validated hoax behaviour questionnaire and analysed through descriptive statistics and the Wilcoxon Signed-Rank Test. Pretest results showed that all participants were categorised as having “high” or “very high” hoax behaviour. After four structured group guidance sessions using the ABCDE model (Activating Event, Belief, Consequence, Disputation, Effect), all students showed a significant behavioural shift to the “low” category. Statistical results confirmed a significant difference between pretest and posttest scores (Z = -2.527, p = 0.012). These findings indicate that the ABCDE technique effectively restructures students’ irrational beliefs and emotional responses, promoting critical thinking, responsible digital behaviour, and ethical media engagement. The study underscores the relevance of incorporating structured psychological interventions such as the ABCDE technique into school counselling programs to foster digital character and strengthen media literacy among adolescents.